2017
DOI: 10.1111/pce.12975
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association studies to identify rice salt‐tolerance markers

Abstract: Salinity is an ever increasing menace that affects agriculture worldwide. Crops such as rice are salt sensitive, but its degree of susceptibility varies widely between cultivars pointing to extensive genetic diversity that can be exploited to identify genes and proteins that are relevant in the response of rice to salt stress. We used a diversity panel of 306 rice accessions and collected phenotypic data after short (6 h), medium (7 d) and long (30 d) salinity treatment (50 mm NaCl). A genome-wide association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 71 publications
1
56
0
1
Order By: Relevance
“…Although the use of brackish and saline water could help alleviate the world's water problems, this option is only possible with the development of salt‐tolerant crops (Figure ) or management practices that alleviate salt stress. A number of manuscripts in this volume (Herzog et al, ; Joshi et al, ; Lakra, Kaur, Anwar, Pareek, & Pareek, ; Oyiga et al, ; Patishtan, Hartley, Fonseca de Carvalho, & Maathuis, ) describe how plants tolerate high levels of salt. Soil phytoremediation and tolerance to heavy metals are also highlighted (Fasani, Manara, Martini, Furini, & DalCorso, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the use of brackish and saline water could help alleviate the world's water problems, this option is only possible with the development of salt‐tolerant crops (Figure ) or management practices that alleviate salt stress. A number of manuscripts in this volume (Herzog et al, ; Joshi et al, ; Lakra, Kaur, Anwar, Pareek, & Pareek, ; Oyiga et al, ; Patishtan, Hartley, Fonseca de Carvalho, & Maathuis, ) describe how plants tolerate high levels of salt. Soil phytoremediation and tolerance to heavy metals are also highlighted (Fasani, Manara, Martini, Furini, & DalCorso, ).…”
Section: Introductionmentioning
confidence: 99%
“…To develop crops tolerant to salinity, it is essential to understand the underlying physiological, molecular, and biochemical mechanisms and identify related genes and gene networks. Patishtan et al () report the results of a genome‐wide association studies of salt‐related traits in 306 rice cultivars. An important region on chromosome 8 was identified that contains a number of genes related to the ubiquitination pathway (Patishtan et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the progress noted above for soybean and Arabidopsis , little is known about the genes shaping natural variation in salinity tolerance in other species. A few traits affected by salinity stress have been investigated via GWAS with high density markers, including traits related to seed germination, growth rate, transpiration rate, and tissue Na + /K + contents in rice (Al‐Tamimi et al, ; Patishtan, Hartley, Fonseca de Carvalho, & Maathuis, ; Shi et al, ), and root growth in Arabidopsis (Kobayashi et al, ). However, no overlapping genes or common mechanisms have been identified among these studies, and none of the identified genes have been validated with respect to salinity tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…It offers advantages over traditional linkage analyses, such as more accurate positioning and mapping, simultaneous assessments of multiple alleles at a locus and no requirement for linkage group construction [ 27 , 28 ]. It has been successfully applied in several crops such as alfalfa, Arabidopsis thaliana , soybean, maize, rice, asparagus bean, Brassica napus , etc., to dissect complex traits including salt and drought tolerance [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. GWAS was also successfully applied in sesame to unravel the genetic basis of its high oil production and quality, and some other key agronomic traits by fully sequencing a population composed of 705 worldwide accessions [ 40 ].…”
Section: Introductionmentioning
confidence: 99%